2019
DOI: 10.1038/s41598-019-39150-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Preoperative Systemic Immune-Inflammation Index in Patients with Cervical Cancer

Abstract: The systemic immune-inflammation index (SII) based on peripheral lymphocyte, neutrophil and platelet counts has been considered a good index that reflects the local immune response and systemic inflammation. However, the use of the SII has not been reported in cervical cancer. In this study, Kaplan-Meier survival analysis showed that a high SII was associated with poor prognosis in cervical cancer patients in the primary and validation cohorts. A higher SII had a significant correlation with larger tumours but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
210
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(259 citation statements)
references
References 37 publications
(37 reference statements)
7
210
3
4
Order By: Relevance
“…No additional records were identified through manual searching. Finally, 9 published articles involving 2724 patients were included in this meta-analysis [11][12][13][14][15][16][20][21][22]. Among these 9 studies, two [11,14] contained the training and validation cohorts from different hospitals, and thus, 11 datasets were totally used for statistical analysis (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…No additional records were identified through manual searching. Finally, 9 published articles involving 2724 patients were included in this meta-analysis [11][12][13][14][15][16][20][21][22]. Among these 9 studies, two [11,14] contained the training and validation cohorts from different hospitals, and thus, 11 datasets were totally used for statistical analysis (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Multivariate analysis proved that increased SII correlated with poor OS (Liu et al: HR = 2.60, 95% CI = 1.74-3.88; P < 0.001 [12]; Wang et al: HR = 2.96, 95% CI = 2.18-3.98; P < 0.00 1 [13]) and DFS (Liu et al: HR = 1.46, 95% CI = 1.01-2.12; P = 0.045 [12]; Wang et al: HR = 2.85, 95% CI = 1.62-3.81; P = 0.005 [13]) in patients with triple-negative breast cancer. Using primary (HR = 2.53, 95% CI = 1.32-4.83; P = 0.005) and validation (HR = 3.99, 95% CI = 1.388-11.47; P = 0.010) cohorts, the study of Huang et al supported that SII was an independent risk factor for prediction of OS in cervical cancer patients [14]. Furthermore, receiver operating characteristics curve analysis suggested that the prognostic accuracy of SII for 5-year OS in patients with cervical cancer was even higher than NLR [area under the curves (AUC): 0.64 vs 0.59, primary; 0.64 vs 0.59, validation] or PLR (AUC: 0.64 vs 0.60, primary; 0.64 vs 0.60, validation) [14], indicating SII may represent a promising biomarker for predicting survival of gynecological cancer patients clinically.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Among them, one concerning cervical cancer was disposed separately cause of providing HRs and survival outcomes for patients with two different treatments [21]. As a consequence, fifteen, nine, and four publications regarding to cervical [19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34], ovarian [35][36][37][38][39][40][41][42][43], and endometrial cancer [44][45][46][47] were enrolled, respectively.…”
Section: Literature Search Results and Characteristicsmentioning
confidence: 99%
“…Consequently, several immune scoring systems were developed based on the immune-related gene expression patterns through integrated analysis of The Cancer Genome Atlas (TCGA) database to explore the relationships between tumor cells and immunocytes in TME, as well as to quantify the immune microenvironment for each individual cancer case. Of them, the in ammation-based index was reported to be associated with the local immune response and prognosis in various cancers, including pancreatic cancer, colorectal cancer [15], non-small cell lung cancer [16] and tongue cancer [17] and so on. However, limited studies have been designed in an attempt to develop an immune-related prognostic signature for EC.…”
Section: Introductionmentioning
confidence: 99%